If my problem is

10 - 2 (x + 3) = 3x + 2
What does x equal?

9 answers

To solve the equation \( 10 - 2 (x + 3) = 3x + 2 \), follow these steps:

  1. Distribute the -2 on the left side: \[ 10 - 2x - 6 = 3x + 2 \]

  2. Simplify the left side: \[ 4 - 2x = 3x + 2 \]

  3. To isolate \( x \), first add \( 2x \) to both sides: \[ 4 = 5x + 2 \]

  4. Next, subtract 2 from both sides: \[ 2 = 5x \]

  5. Finally, divide both sides by 5: \[ x = \frac{2}{5} \]

Thus, the solution is: \[ \boxed{\frac{2}{5}} \]

If my equation is
3(8x+24)/12 = 9 - 3 (x - 4)
What does x equal?

To solve the equation

\[ \frac{3(8x + 24)}{12} = 9 - 3(x - 4), \]

we can start simplifying both sides.

  1. Simplify the left side:

\[ \frac{3(8x + 24)}{12} = \frac{3}{12}(8x + 24) = \frac{1}{4}(8x + 24) = 2x + 6. \]

So the left side becomes:

\[ 2x + 6. \]

  1. Simplify the right side:

Distributing the \(-3\) on the right side gives:

\[ 9 - 3(x - 4) = 9 - 3x + 12 = 21 - 3x. \]

  1. Set the simplified sides equal to each other:

Now we have:

\[ 2x + 6 = 21 - 3x. \]

  1. Solve for \(x\):

Add \(3x\) to both sides:

\[ 2x + 3x + 6 = 21 \implies 5x + 6 = 21. \]

Then subtract \(6\) from both sides:

\[ 5x = 15. \]

Finally, divide by \(5\):

\[ x = 3. \]

Thus, the solution is:

\[ \boxed{3}. \]

2 • (3 + 3b)

To simplify the expression \(2 \cdot (3 + 3b)\), we can distribute the \(2\) to both terms inside the parentheses.

  1. Distribute: \[ 2 \cdot 3 + 2 \cdot 3b \]

  2. Calculate: \[ 6 + 6b \]

Thus, the simplified expression is:

\[ \boxed{6 + 6b} \]

If my equation is 3(7 + 3b) = 6 + 6b
What does b equal?

To solve the equation

\[ 3(7 + 3b) = 6 + 6b, \]

follow these steps:

  1. Distribute the \(3\) on the left side: \[ 3 \cdot 7 + 3 \cdot 3b = 21 + 9b. \]

    So the equation becomes: \[ 21 + 9b = 6 + 6b. \]

  2. Get all terms involving \(b\) on one side of the equation and constant terms on the other side. Subtract \(6b\) from both sides: \[ 21 + 9b - 6b = 6, \] which simplifies to: \[ 21 + 3b = 6. \]

  3. Subtract \(21\) from both sides: \[ 3b = 6 - 21, \] simplifying this gives: \[ 3b = -15. \]

  4. Divide by \(3\) to solve for \(b\): \[ b = \frac{-15}{3} = -5. \]

Thus, the solution is:

\[ \boxed{-5}. \]

-2 • 6

To calculate \(-2 \cdot 6\):

\[ -2 \cdot 6 = -12. \]

So, the result is:

\[ \boxed{-12}. \]